2021
DOI: 10.1097/md.0000000000025379
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of different acupuncture therapies for neck pain

Abstract: Background: Neck pain is common musculoskeletal disorders in adult population. Acupuncture treatment has been widely used for treating neck pain. Nevertheless, previous systematic reviews (SRs) on acupuncture for neck pain remain controversial, and there is no SR for the comparative efficacy and safety of various types of acupuncture. Therefore, this study aims to evaluate and rank the effectiveness and safety of different types of acupuncture for neck pain by SR and network meta-analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Some studies have shown that acupuncture can effectively reduce pain and improve function in patients with CNP, supporting its appropriateness and effectiveness in treating chronic pain. 46 , 47 However, a study using SA found that although the VAS scores in both groups were significantly reduced after therapy, there is no significant difference between groups was detected. 48 Similar to our findings, most clinical outcomes were significantly improved in the TA group compared with those in the SA group, except for the VAS and SAS scores; this may be attributed to the placebo effect of SA.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Some studies have shown that acupuncture can effectively reduce pain and improve function in patients with CNP, supporting its appropriateness and effectiveness in treating chronic pain. 46 , 47 However, a study using SA found that although the VAS scores in both groups were significantly reduced after therapy, there is no significant difference between groups was detected. 48 Similar to our findings, most clinical outcomes were significantly improved in the TA group compared with those in the SA group, except for the VAS and SAS scores; this may be attributed to the placebo effect of SA.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, TA showed effectiveness in improving secondary clinical outcomes including the NDI, NPQ, MPQ, SAS, and SDS, as well as, in increasing the SF‐12 scores. Some studies have shown that acupuncture can effectively reduce pain and improve function in patients with CNP, supporting its appropriateness and effectiveness in treating chronic pain 46,47 . However, a study using SA found that although the VAS scores in both groups were significantly reduced after therapy, there is no significant difference between groups was detected 48 .…”
Section: Discussionmentioning
confidence: 99%
“…[17,18] This study was registered on PROSPERO under number CRD42021235274, and a detailed protocol was published elsewhere. [19] 2.1. Search strategy Ovid-MEDILINE, EMBASE, Cochrane library, China National Knowledge Infrastructure (CNKI), Korea Med, Korean medical database (KMBASE), Korean Studies Information Service System (KISS), ScienceON, and Oriental Medicine Advanced Searching Integrated System (OASIS) were searched on July 1, 2021, with the limitation of Chinese, English, and Korean language.…”
Section: Methodsmentioning
confidence: 99%
“…[17,18] This study was registered on PROSPERO under number CRD42021235274, and a detailed protocol was published elsewhere. [19]…”
Section: Methodsmentioning
confidence: 99%